Taeniasis - Oliveira, Letícia Fadda Melo; Simões, Larissa de Oliveira Mendes; Elias, Amanda Luísa Motti de Oliveira; Alvarenga, Janaina Sousa Campos; Alvarenga, Ângela Cardoso de (Seven Editora, 2024)
Introduction: The chapter deals with taeniasis, an infection of the small intestine caused by two cestoids, Taenia solium and Taenia saginata, popularly known as tapeworms or solitaria. Belonging to the class Cestoda, these hermaphrodite parasites have dorsoventrally flattened bodies, devoid of a general cavity and digestive system. Objectives: The focus of the chapter is to provide an in-depth understanding of the clinical, epidemiological, and control strategies related to taeniasis. Etiologic Agent: In man, the definitive host, taeniasis is caused by the presence of the adult form of these parasites in the small intestine. Evolutionary forms: Throughout the biological cycle, both species go through three evolutionary forms: egg, cysticercus, and adult worm. The cysticercus, a larval form, reaches up to 12 mm in length after 4 months of infection. Form of contamination of human beings: Taeniasis, caused by Taenia solium and Taenia saginata is a parasitosis that exclusively impacts humans, and its transmission is associated with the consumption of meat contaminated with cysticerci, the larval forms of the parasite. Infection occurs when individuals ingest contaminated beef or pork, especially if eaten raw or undercooked. Biological cycle: The biological cycle is similar for both species, differing in intermediate hosts. Parasitized humans eliminate pregnant proglottids into the environment, releasing eggs that contaminate soil. Pigs and cattle ingest these eggs, developing cysticerci in the tissues. Human infection occurs through the consumption of contaminated meat. Clinical manifestations: Although the popular designation suggests a single tapeworm, individuals may be infected by more than one, including different species. Most are asymptomatic, but gastrointestinal symptoms, allergies, bleeding spots, and even parasitic appendicitis can occur. Diagnosis: Diagnosis requires laboratory tests, such as screening for proglottids and eggs in the stool. Treatment: The main treatment is Praziquantel, given orally as a single dose. Other medications, such as Mebendazole and Albendazole, are also options. Prophylaxis: Preventive measures include treatment of carriers, basic sanitation, care in raising animals for slaughter, health education, modernization of pig farming, and rigorous inspection of slaughterhouses. Specific strategies, such as avoiding coprophagic behavior in pigs, have been shown to be effective. Conclusion: The chapter provides a comprehensive overview of taeniasis, highlighting its clinical complexity, epidemiological factors, and control approaches. Understanding these aspects is crucial for the effective confrontation of this parasitosis, especially in regions where sanitary and socioeconomic conditions contribute to its dissemination. DOI:https://doi.org/10.56238/sevened2024.001-061